Basic Reproduction Number of Enterovirus 71 and Coxsackievirus A16 and A6: Evidence From Outbreaks of Hand, Foot, and Mouth Disease in China Between 2011 and 2018. (15th December 2020) - Zhang, Zhong; Liu, Yang; Liu, Fengfeng; Ren, Minrui; Nie, Taoran; Cui, Jinzhao; Chang, Zhaorui; Li, Zhongjie
Abstract: Background: Enterovirus 71 (EV-A71), coxsackievirus A16 (CV-A16), and coxsackievirus A6 (CV-A6) are common serotypes causing hand, foot, and mouth disease (HFMD). Analyses on the basic reproduction number ( R 0 ) of common pathogens causing HFMD are limited and there are no related studies using field data from outbreaks in mainland China. Methods: We estimated the pathogen-specific basic reproduction number based on laboratory-confirmed HFMD outbreaks (clusters of ≥10 HFMD cases) reported to the national surveillance system between 2011 and 2018. The reproduction numbers were calculated using a mathematical model and the cumulative cases during the initial growth periods. Results: This study included 539 outbreaks, of which 198 were caused by EV-A71, 316 by CV-A16, and 25 by CV-A6. All 10 417 cases involved were children. Assuming the outbreaks occurred in closed systems and the incubation period is 5 days, the median (interquartile range [IQR]) R 0 estimates of EV-A71, CV-A16, and CV-A6 were 5.06 (2.81, 10.20), 4.84 (3.00, 9.00), and 5.94 (3.27, 10.00). After adjusting for seroprevalences, the R 0 (IQR) estimates for EV-A71, CV-A16 (optimistic and conservative scenarios), and CV-A6 were 12.60 (7.35, 25.40), 9.29 (6.01, 19.20), 15.50 (9.77, 30.40), and 25.80 (14.20, 43.50), respectively. We did not observe changes in the R 0 of EV-A71 after vaccine licensure ( P = .67). Conclusions: HFMD is highly transmissible when caused by the 3 most common serotypes. In mainland China, it primarily affects young children. Although a vaccine became available in 2016, we have not yet observed any related changes in the disease dynamics. Abstract : This study estimates the pathogen-specific basic reproduction number based on laboratory-confirmed hand, foot, and mouth disease outbreaks in China between 2011 and 2018. It is the first to compare the changes in R 0 before and after the EV-A71 vaccine licensure.